ENGLISH-MEDIUM INSTRUCTION IN ASIAN EFL HIGHER EDUCATION: A SYSTEMATIC REVIEW OF POLICY TRENDS, IMPLEMENTATION CHALLENGES, AND ADAPTIVE STRATEGIES - Ahmad Saifulloh; Muhammad Arif Al Hakim (IJEE (Indonesian Journal of English Education), 2026)
The expansion of English Medium Instruction (EMI) across Asian higher education has intensified post-pandemic, yet a comprehensive understanding of its implementation landscape remains limited. Following PRISMA 2020 guidelines, this systematic review synthesizes 15 empirical studies (2015–2025) from four academic databases to explore implementation trends, stakeholder challenges, and adaptation strategies in Asian EFL contexts. Frequency analysis revealed that linguistic difficulties were a primary barrier in 87% of the studies, pedagogical inconsistency in 60%, and language anxiety affected 53% of the combined participants. Thematic synthesis identified three core dimensions: top-down policies generating macro-micro gaps and institutional stratification; multidimensional linguistic and psychological barriers impacting engagement; and emergent adaptive strategies, including translanguaging, bilingual professional learning communities, and learner metacognition. These findings highlight that EMI is a complex educational ecosystem rather than a mere linguistic shift. This review offers a structured, geographically scoped framework for policymakers, institutions, and future researchers to improve EMI quality and equity in the region.